The Covid-19 Pandemic and its Influence on Murabahah Financing in Indonesian Islamic Banking - Nisa, Uswatun; Marta Rini, Disti; Hasan, Zulfikar (STAIN Bengkalis, 2023)
In 2019, people around the world, especially in Indonesia, were shocked by the disaster of a pandemic, where this pandemic is an epidemic that spreads, an example of a disease that has become a pandemic is coronavirus disease 2019 (covid-19). This pandemic is a disease that everyone must be very aware of because this disease spreads unnoticed. The impact of this pandemic has great potential for the economic and financial sectors, especially in the banking world, where in a pandemic like this to seek additional capital, it is large companies that can provide loans or financing, such as Islamic banks with all the products provided in these banks. one of them is murabahah financing which is very suitable for those who want to open a business but do not yet have additional capital, this tendency is for murabahah financing, the risk of financing is smaller, the margins are lower, and the administrative costs are also low. This study uses the literature study method by obtaining and collecting data from various previous studies related to the effect of the pandemic on Murabaha financing in Islamic banks. The research method used is literature study, and data collection uses the library study method. For this reason, the authors recommend improving strategies for the risks faced by Islamic banks, especially during a pandemic like this, and making the best possible use of the products owned by the banks themselves and developing them to improve the quality of Islamic banks themselves.